Near‐Infrared Fluorescence from Silicon‐ and Nickel‐Based Color Centers in High‐Pressure High‐Temperature Diamond Micro‐ and Nanoparticles. Issue 23 (1st October 2020) - Shames, Alexander I.; Dalis, Adamos; Greentree, Andrew D.; Gibson, Brant C.; Abe, Hiroshi; Ohshima, Takeshi; Shenderova, Olga; Zaitsev, Alexander; Reineck, Philipp
Abstract: Fluorescent color centers in diamond are invaluable room temperature quantum systems in fundamental scientific studies and vital for many emerging applications from inertial navigation to quantum sensing in biology. Yet, controlled production of specific color centers in synthetic diamond at scale remains challenging. Characteristics of silicon‐ and nickel‐based defects with strong fluorescence in the 700–950 nm spectral region formed in Si‐ and Ni‐doped diamond, created via high‐pressure high‐temperature synthesis in commercial quantities without irradiation, are reported. Using electron paramagnetic resonance spectroscopy and fluorescence spectroscopy, the presence of defects including the negatively charged silicon‐vacancy (SiV − ), silicon‐boron (SiB) and positively charged substitutional nickel center (Nis + ) in micrometer‐sized particles is identified and quantified. The color centers' optical properties are investigated via time‐resolved and steady‐state fluorescence spectroscopy below 10 K and at room temperature. In ensemble measurements, the particles show no detectable signals from nitrogen‐vacancy (NV − ) defects. The particles' relative fluorescence brightness is quantified and compared to particles containing ≈1 ppm NV − centers. It is demonstrated that the Nis + center fluorescence characteristics are preserved in 50 nm nanoparticles. The work paves the way for the use of fluorescent nanodiamonds in the first near‐infrared biological window between 700 nm and 950 nm in biomedical applications. Abstract : Near‐infrared fluorescent color centers in diamond hold promise for many applications. Here, silicon‐ and nickel‐doped diamond particles with fluorescence above 700 nm are investigated. Using electron paramagnetic resonance and fluorescence spectroscopy, three color centers are identified in micron‐sized particles, and their fluorescence properties characterized. Nis + center fluorescence above 850 nm is preserved in nanoparticles, boding well for bioimaging applications.